Receptor binding profiles and behavioral pharmacology of ring-substituted N, N-diallyltryptamine analogs. (November 2018) - Klein, Landon M.; Cozzi, Nicholas V.; Daley, Paul F.; Brandt, Simon D.; Halberstadt, Adam L.
Abstract: Substantial effort has been devoted toward understanding the psychopharmacological effects of tryptamine hallucinogens, which are thought to be mediated by activation of 5-HT2A and 5-HT1A receptors. Recently, several psychoactive tryptamines based on the N, N -diallyltryptamine (DALT) scaffold have been encountered as recreational drugs. Despite the apparent widespread use of DALT derivatives in humans, little is known about their pharmacological properties. We compared the binding affinities of DALT and its 2-phenyl-, 4-acetoxy-, 4-hydroxy-, 5-methoxy-, 5-methoxy-2-methyl-, 5-fluoro-, 5-fluoro-2-methyl-, 5-bromo-, and 7-ethyl-derivatives at 45 receptor and transporter binding sites. Additionally, studies in C57BL/6 J mice examined whether these substances induce the head twitch response (HTR), a 5-HT2A receptor-mediated response that is widely used as a behavioral proxy for hallucinogen effects in humans. Most of the test drugs bound to serotonin receptors, σ sites, α2 -adrenoceptors, dopaminergic D3 receptors, histaminergic H1 receptors, and the serotonin transporter. DALT and several of the ring-substituted derivatives were active in the HTR assay with the following rank order of potency: 4-acetoxy-DALT > 5-fluoro-DALT > 5-methoxy-DALT > 4-hydroxy-DALT > DALT > 5-bromo-DALT. 2-Phenyl-DALT, 5-methoxy-2-methyl-DALT, 5-fluoro-2-methyl-DALT, and 7-ethyl-DALT did not induce the HTR. HTR potency was not correlated with either 5-HT1A or 5-HT2A receptor binding affinity, but a multiple regression analysis indicated that 5-HT2A and 5-HT1A receptors make positive and negative contributions, respectively, to HTR potency ( R 2 = 0.8729). In addition to supporting the established role of 5-HT2A receptors in the HTR, these findings are consistent with evidence that 5-HT1A activation by tryptamine hallucinogens buffers their effects on HTR. This article is part of the Special Issue entitled 'Psychedelics: New Doors, Altered Perceptions'. Highlights: A new class of recreational drugs are derived from N, N -Diallyltryptamine (DALT). DALT derivatives are relatively nonselective for serotonin receptors. DALT derivatives induce the head twitch response (a 5-HT2A -mediated behavior) in mice. Both 5-HT2A and 5-HT1A receptors contribute to head twitch potency.